1966
DOI: 10.1001/jama.1966.03110230098021
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tissue Temperatures and Blood Flow on Motor Nerve Conduction Velocity

Abstract: (Fig 1). The temperature of the skin, subcutaneous tissue, and muscle (at an aver¬ age depth of 3.5 cm in the brachioradialis muscle group) was determined, using copper constantan thermocouples, while motor conduction velocity of the segments of ulnar and median nerves coursing through the portion of the limb enclosed in the ple¬ thysmograph was measured according to the meth¬ od of Thomas et al8 (Fig 1)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
70
0
1

Year Published

1972
1972
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(75 citation statements)
references
References 4 publications
4
70
0
1
Order By: Relevance
“…The arms of subjects in the other 2 groups, who were not exposed to the heat of the Fluidotherapy unit, did not demonstrate a decrease in SNAP latency. This inverse relationship between cutaneous temperature and SNAP latency supports the findings of Abramson et al 1 and Greathouse et al, 6 among others. 2,5,8,15 However, this is the first study to have demonstrated this relationship as a result of Fluidotherapy treatment.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The arms of subjects in the other 2 groups, who were not exposed to the heat of the Fluidotherapy unit, did not demonstrate a decrease in SNAP latency. This inverse relationship between cutaneous temperature and SNAP latency supports the findings of Abramson et al 1 and Greathouse et al, 6 among others. 2,5,8,15 However, this is the first study to have demonstrated this relationship as a result of Fluidotherapy treatment.…”
Section: Discussionsupporting
confidence: 86%
“…Madsen and Gersten, 16 as well as Zankel,25 documented decreased conduction velocities of various motor nerves and the ulnar nerve following ultrasound application. However, the balance of literature has reported an inverse linear relationship between latency and temperature change, 1,2,5,6,8,15 with increasing temperature resulting in decreased latency (increased conduction velocity). Abramson et al 1 demonstrated increased conduction velocity of the median and ulnar ner ves following shortwave diathermy and topically applied heat.…”
mentioning
confidence: 99%
“…Cold therapy has also been found to be beneficial after injury or operation by slowing pain signal transmission [1], local affects on tissue metabolism via decreasing enzyme function, and local vasoconstriction [3].…”
Section: Introductionmentioning
confidence: 99%
“…Muscle activity intensity displayed a similar trend in Eurycea, another plethodontid salamander (Anderson et al, 2014), but is independent of temperature during tongue projection in toads (Deban and Lappin, 2011) and chameleons (Anderson and Deban, 2012). The precise physiological limitations underlying reduced muscle activity intensity at low temperatures in plethodontid salamanders is not known, but may stem from changes in motor unit recruitment or reduced nerve conduction at low temperatures (Abramson et al, 1966;Rome et al, 1984;Jayne et al, 1990;Hill et al, 2008).…”
Section: Intensity Of Muscle Activitymentioning
confidence: 99%